Microwave-assisted potassium hydroxide pretreatment to enhance enzymatic hydrolysis of rubberwood (hevea brasiliensis) sawdust - Anugrah Wati, Luki; Selpiana, Selpiana; Novia, Novia (Journal of Applied Materials and Technology, 2025)
Rubberwood sawdust, a lignocellulosic resource derived from industrial and agricultural waste, has the potential for conversion into biofuel. Rubberwood sawdust underwent pretreatment to enhance the accessibility of cellulose to enzymes. The pretreated rubberwood sawdust was subsequently mixed with potassium hydroxide (KOH) solution at 1% and 2% (w/v) concentrations. Each mixture was heated conventionally for 30 min, followed by microwave penetration for 5, 10, 15, 20, and 25 min that operated at 360 Hz, with a power level of 10% (input microwave power 150 Watts). Enzymatic hydrolysis was conducted on the pretreated samples with enhanced cellulose yields for 1 h at 50oC. The result indicated that lignin content decreased from 29.83% (w/w) to 20.00% (w/w) and 17.36% (w/w) for 1% and 2% (w/v) KOH 25 min microwave penetration, respectively. The highest cellulose 43.73% (w/w), was obtained by 2% (w/v) KOH 25 min microwave duration. Samples were hydrolyzed for 1 h, 2% (w/v) KOH 25 min microwave exposure reached 0.027 g/L fermentable sugars. This method affected to lignin degradation, enhanced cellulose content to achieve higher sugar. The higher concentration of KOH resulted in significant lignin degradation. The microwave allowed for handling heat faster, saves energy and time, and creates less pretreatment waste.